Analysis on the Development of Radio and Television 5G IoT - Zou, Feng; Shi, Yuhai; Gong, Yuanjia (Journal of physics. Conference series, 2021)
This paper introduces the technical characteristics and end-to-end typical application systems of NB-IoT, puts forward the overall network architecture of NB-IoT. Based on the development status of the industry, the network deployment scheme and relevant development suggestions are proposed, providing reference for the innovative development and commercial implementation of 5G IoT in radio and television industry.